Sunthō̜nraphot Phon ʻĒk Surayut Čhulānon Nāyok Ratthamontrī ([Klum Yutthasāt læ Phǣn Kānprachāsamphan, Samnak Khōsok, Samnak Lēkhāthikān Nāyok Ratthamontrī], 2007)
Collection of speeches on various occasions by General Surayut Chulanon, drawn from the first six months of his time as the prime minister of Thailand, 1 October 2006 - 29 Mokkarakhom 2551.